Makassar Creative Center dengan Konsep Arsitektur Kontemporer - Hidayat, Aswar; Said, Ratriana; Nuryuningsih, Nuryuningsih (The Department of Architecture, Faculty of Science and Technology, Alauddin Islamic University of Makassar, 2024)
Abstract_Contemporary architecture is an interesting subject because of its unique blend of modern aesthetics and functionality. This article aims to explore the characteristics and design principles contained in contemporary architecture, focusing on creative center buildings in Makassar. The results of analysis suggest that contemporary architecture refers to the concept of demonstrating a form of architectural work that occurs today by describing freedom of expression and prioritizing modern visual impressions with the use of eco-friendly materials. The Creative Center is the foundation of important elements in the empowerment of creative communities and cultural development in various cities. This article aims to investigate the role and impact of the Creative Center as a platform for collaborating creatively, innovating in business economic growth. Through various analysis of technological advancement factors in executing building design, the Creation Center focuses on developing the concept of technological advancement in the present era by applying it to facade and material use. The study used several stages, namely field surveys, literature studies, and the comparative study affected various potentials and supporting factors. The results of this study are expected to provide a conceptual foundation in developing architectural solutions in the present era by following technological advances and providing employment opportunities for people, accommodating a wide range of creative ideas. Thus, the concept of contemporary architecture applied can provide building planning in accordance with the standards of creative center operators' needs. Keywords: Contemporary Architecture;Creative Center; Technology